THE EFFECT OF TIME TRAPS AND PSYCHOLOGICAL CAPITAL ON WORKPLACE PROCRASTINATION IN SERVICE SECTOR EMPLOYEES (Third Sector Social Economic Review, 2024)
Workplace procrastination, which occurs when human resources postpone their tasks to a later date despite being aware of all the negativities that may arise, is an important problem for all sectors, especially the service sector, as it negatively affects productivity and service quality and reduces overall organizational performance. In this context, recognizing and understanding the factors that contribute to workplace procrastination is crucial for developing effective strategies to combat it. Based on this point, the aim of this study is to determine the regulatory role of psychological capital in the effect of time traps on workplace procrastination. The study included 396 people working in the service sector throughout Istanbul. SPSS 26.00 and Smart PLS 4 were used for data analysis and structural equation modeling was used to test the research hypotheses.According to the findings, while time traps increase workplace procrastination, all psychological capital factors including optimism, psychological resilience, hope and self-efficacy decrease workplace procrastination. According to the results of the analysis for the moderating role, all of the psychological capital factors consisting of optimism, psychological resilience, hope and self-efficacy have a moderating role in the effect of time traps on workplace procrastination. Accordingly, psychological capital reduces the effect of time traps on workplace procrastination. As a strategic intervention to reduce the effect of time traps on workplace procrastination, the development of psychological capital consisting of optimism, psychological resilience, hope, and self-efficacy has an important role to play and targeted organizational and individual-level strategies aimed at developing these psychological resources should be developed to foster a more productive and engaged workforce.
Keywords: Time traps; psychological capital; workplace procrastination.